The Shift in Feedback Loops: Exploring Generative AI-Augmented Supervisory Discourse in Indonesian Doctoral Education - Sahril Nur; Geminastiti Sakkir; Auliyanti Sahril Nurfadhilah (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This research investigates the transformation of doctoral supervisory discourse from dyadic to triadic interactions through Generative Artificial Intelligence (GenAI) in Indonesia. Utilizing a qualitative case study and Computer-Mediated Discourse Analysis (CMDA) of ten supervisory triads, the study examines how AI-augmented loops influence Scholarly Dignity, well-being, and persistence. By synthesizing the PERMA and HOPE models with the indigenous philosophy, findings reveal that GenAI functions as a